2015
DOI: 10.1615/jlongtermeffmedimplants.2015011695
|View full text |Cite
|
Sign up to set email alerts
|

Marrow Stem Cell Differentiation for Valvulogenesis via Oscillatory Flow and Nicotine Agonists: Unusual Suspects?

Abstract: Fluid-induced oscillatory shear stress (OSS) and nicotine are known antagonists in cardiovascular disease. However, from a regenerative medicine standpoint, we hypothesized that these parameters may support the cell differentiation of bone marrow mesenchymal stem cells (BMMSCs) for engineering heart valves. In this study, OSS and nicotine (10-6M) were applied individually to BMMSCs in monolayer culture. In both cases, a significantly higher expression of CD31 was detected compared to corresponding controls (p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Average intensity of the ROIs was recorded in arbitrary units (AU). Care was taken to avoid any false positive signals [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Average intensity of the ROIs was recorded in arbitrary units (AU). Care was taken to avoid any false positive signals [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory has previously demonstrated that HBMSC-derived tissue formation and flow-responsive differential regulation is robust when cell-seeded constructs are cultured under fluid-induced PSS environments. Spatial distribution of HBMSCs that differentiated to the endothelial phenotype (CD31+) were largely found on the tissue surfaces, while cells with an activated myofibroblast phenotype (αSMA +) were mostly aggregated in the interstitial space, similar to the native heart valve cellular-makeup ( 12 , 13 , 26 , 27 ). Specifically, PSS regulates HBMSCs structure and has been shown to be highly relevant to both native heart valve development and to TEHVs ( 27 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine may stimulate an increase in the differentiation of BMSCs to endothelial cells, OSS may play a greater role in cellular distribution, and the eventual creation of a tissue engineered heart valves (TEHV) endothelium [157].…”
Section: Resultsmentioning
confidence: 99%